Penguatan Kompetensi Profesional Guru Sekolah Dasar Di Abad 21 - Syawitri, Damar (CV. SINAR HOWUHOWU, 2025)
This study aims to identify the factors influencing the strengthening of the professional competence of elementary school teachers in the 21st century and to explore the challenges and strategies implemented in enhancing these competencies. A qualitative descriptive approach was used, with data collection methods including in-depth interviews, participatory observations, and document analysis. The findings of the study indicate that education policies, continuous training, school management support, and the use of technology are key factors in strengthening teacher competence. Although various policies and training programs have been implemented, challenges such as limited access to technology and high administrative burdens remain significant barriers. This study recommends the improvement of access to technology, reduction of administrative burdens, and strengthening of structured professional development policies. By doing so, the strengthening of teachers' professional competence can be optimized, leading to an enhancement in the quality of elementary education in Indonesia.